(3/29 - 1/15 ) x 29/3
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a,3/29.29/3-1/15.29/3=1-29/45=16/45
b,23/27(7/9-5/9-1)=23/27(-7/9)=161/243
\(\frac{-15}{29}.\frac{7}{8}-\frac{15}{29}.\frac{3}{8}+\frac{15}{29}:\frac{4}{3}\)
\(=\left(\frac{-15}{29}\right)\left(\frac{7}{8}+\frac{3}{8}-\frac{6}{8}\right)\)
\(\left(\frac{-15}{29}\right).\frac{1}{2}=\frac{-15}{58}\)
-15/29 . 7/8 - 15/29 . 3/8 + 15/29 : 4/3 = 15/29 . -7/8 - 15/29 . 3/8 + 15/29 . 3/4
=15/29 . ( -7/8 - 3/8 + 3/4)
=15/29. -1/2
=-15/58
a)15/16:3/8x3/4
=15/16:6/16x12/16
=15/16x16/6x12/16
=15/6x12/16
=30/16=15/8
b)5/11x18/29-5/11x8/29+5/11x19/29
=5/11x(18/29-8/29+19/29)
=5/11x1=5/11
1) PT \(\Leftrightarrow\left(\dfrac{x+1}{35}+1\right)+\left(\dfrac{x+3}{33}+1\right)=\left(\dfrac{x+5}{31}+1\right)+\left(\dfrac{x+7}{29}+1\right)\)
\(\Leftrightarrow\dfrac{x+36}{35}+\dfrac{x+36}{33}=\dfrac{x+36}{31}+\dfrac{x+36}{29}\)
\(\Leftrightarrow\left(x+36\right)\left(\dfrac{1}{29}+\dfrac{1}{31}-\dfrac{1}{33}-\dfrac{1}{35}\right)=0\)
\(\Leftrightarrow x+36=0\) (Do \(\dfrac{1}{29}+\dfrac{1}{31}-\dfrac{1}{33}-\dfrac{1}{35}>0\))
\(\Leftrightarrow x=-36\).
Vậy nghiệm của pt là x = -36.
2) x(x+1)(x+2)(x+3)= 24
⇔ x.(x+3) . (x+2).(x+1) = 24
⇔(\(x^2\) + 3x) . (\(x^2\) + 3x + 2) = 24
Đặt \(x^2\)+ 3x = b
⇒ b . (b+2)= 24
Hay: \(b^2\) +2b = 24
⇔\(b^2\) + 2b + 1 = 25
⇔\(\left(b+1\right)^2\)= 25
+ Xét b+1 = 5 ⇒ b=4 ⇒ \(x^2\)+ 3x = 4 ⇒ \(x^2\)+4x-x-4=0 ⇒x(x+4)-(x+4)=0
⇒(x-1)(x+4)=0⇒x=1 và x=-4
+ Xét b+1 = -5 ⇒ b=-6 ⇒ \(x^2\)+3x=-6 ⇒\(x^2\) + 3x + 6=0
⇒\(x^2\) + 2.x.\(\dfrac{3}{2}\) + (\(\dfrac{3}{2}\))2 = - \(\dfrac{15}{4}\) Hay ( \(x^2\) +\(\dfrac{3}{2}\) )2= -\(\dfrac{15}{4}\) (vô lí)
⇒x= 1 và x= 4
1,7-(18+x)=-15
<=>18+x=7+15
<=>18+x=22
<=>x=4
2,(x-17)-(-3)=0
<=>x-17+3=0
<=>x-17=-3
,<=>x=14
<=>
1,
7 - ( 18 + x ) = - 15
18 + x = 7 + 15
18 + x = 22
x = 22 - 18
x = 4
2,
( x - 17 ) - ( - 3 ) = 0
( x - 17 ) + 3 = 0
x - 17 = - 3
x = -3 + 17
x = 14
3, -18 - ( x - 6 ) = 0
-18 = x- 6
x = - 18 + 6
x = - 12
4, 29 - ( 10 + 29 ) = x - ( 27 - 9 )
-10 = x - 18
x = - 10 + 18
x = 8
a) (2/5 x 25/29) + (3/5 x 25/29)
= (50/145) + (75/145)
= 125/145
b) (5/2 x 3/7) - (3/14 : 6/7)
= 15/14 - (3/14 x 7/6)
= 15/14 - 1/2
= (30/28) - (14/28)
= 16/28
= 4/7
c) (15/4 : 5/12) - (6/5 : 11/15)
= (15/4 x 12/5) - (6/5 x 15/11)
= 180/20 - 90/55
= 9 - 18/11
= (99/11) - (18/11)
= 81/11
= 7 4/11
a) (2/3) + (20/21 x 3/2 x 7/5)
= 2/3 + (60/210)
= 2/3 + 2/7
= (14/21) + (6/21)
= 20/21
b) (5/17 x 21/32 x 47/24 x 0)
= 0
c) (11/3 x 26/7) - (26/7 x 8/3)
= (286/21) - (208/21)
= 78/21
= 3 9/21
= 3 3/7
a) (25/8) : x = 5/16
=> (25/8) x (16/5) = x
=> 4 = x
b) x + (7/15) = 6/15
=> x = (6/15) - (7/15)
=> x = -1/15
c) x : (28/49) = 7/12
=> x x (49/28) = 7/12
=> x = (7/12) x (28/49)
=> x = 1/2
a) 6 x x = (5/8) : (3/4)
=> 6x = (5/8) x (4/3)
=> 6x = 20/24
=> 6x = 5/6
=> x = (5/6) / 6
=> x = 5/36
câu,b,không,đủ,thông,tin,nhan,bạn.
\(=4+\dfrac{5}{58}-3-\dfrac{1}{2}+8+\dfrac{15}{29}-3-\dfrac{5}{58}+7+\dfrac{14}{29}=13+\dfrac{1}{2}=\dfrac{27}{2}\)
-29.(85-47)-85.(47-29)
=-29.38-85.18
=-1102-1503
=-2605
-15.(23-29)+23-(15-29)
=-15.(-6)+23-(-14)
=90+23+14
=113+14
=127
-13.(55-29)+23.(15-29)
=-13.26+23.(-14)
=-338+(-322)
=-660
-10.(2+4)-5.(4-3)
=-10.6-5.1
=-60-5
=-65
`(3/29-1/15) xx 29/3`
`=3/29 xx 29/3 - 1/15 xx 29/3`
`=1 - 29/45`
`=16/45`
=\(\dfrac{16}{45}\)